Field investigations of a smiley-face polling station for recording occupant satisfaction with indoor climate. (November 2020) - Lassen, Niels; Goia, Francesco; Schiavon, Stefano; Pantelic, Jovan
Abstract: The use of smiley-face polling stations has had a rapid growth as a means of automatically and efficiently collecting user satisfaction verdicts in airports, restrooms, museums, and retail. Their advantages are that they are low cost, efficient for both respondents and analysts, in addition to having higher response rates than other survey types. Their main disadvantage is the lack of control with who is voting, meaning both repeat voters and non-voters may lead to biased results. The aim of this study is to assess the representativeness and functioning of such publicly located satisfaction polling stations (SPSs) in an indoor climate setting, and to evaluate their potential for real-time evaluation of occupant's satisfaction with the indoor climate. We carried out continuous field tests in two office buildings for more than two months where the results of SPSs were compared with 473 survey results collected in 10 rounds during the tests. To assess how sensitive the instrument was to changing conditions, we deliberately changed temperature setpoints on selected days in one of the buildings. We found that the SPSs had a high and variable non-response bias which could result in a low accuracy for benchmarking of building indoor climate satisfaction. Results also showed a high correlation between SPS complaints and complaints recorded in the surveys for the thermal comfort aspect of indoor climate, including thermal comfort induced by temperature interventions. SPSs can provide valuable continuous recordings of the occupant's satisfaction with the indoor climate. Graphical abstract: Image 1 Highlights: Effectiveness of SPSs to quantify satisfaction with IEQ in 2 office buildings is measured. SPS sensitivity to environmental changes is investigated by changing temperature setpoint. Results showed high and variable non-response bias. Results showed high correlation between SPS complaints and survey complaints. Voting frequency declined during the first two weeks and stabilized at ca. 30% daily votes of population.